2018
DOI: 10.1111/1477-9552.12290
|View full text |Cite
|
Sign up to set email alerts
|

Saying Sayonara to the Farm: Hierarchical Bayesian Modeling of Farm Exits in Japan

Abstract: Off-farm employment opportunities are thought to have an effect on farm exit rates, though evidence on the sign of this effect has been mixed. Examining this issue in the context of Japanese agriculture, we find that farm exits are related to off-farm income as a share of household income, and more specifically to the nature of off-farm work. Two econometric models are developed: a hierarchical Bayesian linear model and a hierarchical Bayesian Poisson model. Both models perform well in predicting exit rates ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
(43 reference statements)
1
7
0
Order By: Relevance
“…Similar trends have been reported in Africa, where 2.11% growth (2003-2008), and 1.73% growth (2008-2015) labour productivity was reported [82]. In contrast to the findings of the present study, [83] reported consistently falling Japanese agricultural production due labour shortages and significant migration of rural agriculture to off-farm income in urban areas.…”
Section: Strengthssupporting
confidence: 84%
“…Similar trends have been reported in Africa, where 2.11% growth (2003-2008), and 1.73% growth (2008-2015) labour productivity was reported [82]. In contrast to the findings of the present study, [83] reported consistently falling Japanese agricultural production due labour shortages and significant migration of rural agriculture to off-farm income in urban areas.…”
Section: Strengthssupporting
confidence: 84%
“…This also applies to part-time farming (see RIRDC, 2007; Martini and Kimura, 2009; NFU, 2011; Antman et al. , 2015; Ramsey et al. , 2019), which has a below-average role in South Africa's commercial farms.…”
Section: Applying Structural Change Theory To South Africa's Commerci...mentioning
confidence: 99%
“…, 2015; Lowder et al. , 2016; European Commission, 2017; Shimizu, 2017; Padmanabhan, 2018; Ramsey et al. , 2019), it became clear that three categories of factors appeared to have the largest effect on the change in producer numbers, whether increasing or decreasing it.…”
Section: Applying Structural Change Theory To South Africa's Commerci...mentioning
confidence: 99%
See 2 more Smart Citations